Relationship of Clinical Data and Confirmed Case of COVID-19, in the Mexican State of Guanajuato - Nicolas Padilla-Raygoza; Gilberto Flores-Vargas; María de Jesús Gallardo-Luna; Efraín Navarro-Olivos (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Aims: The objective was to analyze the clinical data in the population from Mexican Guanajuato state as a suspected case of COVID-19 and with result positive of rRT-PCR, reported until October 2, 2020. Intorduction: Since the beginning of the new coronavirus pandemic in Wuhan, China, at the end of 2019 , one of the concerns has been to have a precise diagnosis. Fever is the most reported sign in COVID-19 cases , but it is also present in other viral infections. Study Design: It is a cross-sectional study based on the data from the National Epidemiological Surveillance System of the General Epidemiological Directorate, from the Mexican Secretary of Health. Place and Duration of Study: Sample registries from confirmed and discarded cases of COVID-19 in the database until October 2, 2020. Methodology: 100,919 registries were considered. Among them, 810 were excluded due to the absence of the result of rRT-PCR test. A suspected case was one with a clinical finding considered greater (cough, fever, headache, or dyspnea and accompanied by at least one of the following: myalgia, arthralgia, odynophagia, chills, chest pain, rhinorrhea, anosmia, dysgeusia, or conjunctivitis); a confirmed case of COVID-19 is a person with a positive rRT-PCR test for SARS-CoV-2, regardless of the clinical data presented. We included age, sex, and clinical data registered and the result of rRT-PCR for SARS-CoV-2. It was used logistic regression to analyze the effect of clinical data on positive rRT-PCR. Results: It was analyzed 100,109 registries. From them, 41,734 were positive for SARS-CoV-2. Fever (OR 1.72, CI95% 1.68 to 1.77), cough (OR 1.70, CI95% 1.66 to 1.74), and odynophagia (OR 1.71, CI95% 1.66 to 1.75) shown a stronger effect on positive rRT-PCR test. Cyanosis did not have any effect on the result of the rRT-PCR test. Conclusion: There are no pathognomonic clinical data for COVID-19. All clinical data in confirmed cases are like other respiratory viral infections.